QUALITY ASSURANCE OF NON-FORMAL ADULT EDUCATION DEVELOPMENT - Zakrevska, Svitlana (Continuing Professional Education: Theory and Practice, 2019)
The article analyzes the problem of quality assurance in a non-formal adult education sector. The theoretical concept of the article is based on the idea of the qualitative development of civil society in Ukraine. An example of higher and youth education shows the importance of an integrated approach and systematic analysis of external and internal factors in the implementation of this task in the field of adult non-formal education. The article emphasizes the idea that it is important for Ukraine to pay attention to an integrated approach to the development of quality assurance system, transparency and better understanding of non-formal education in terms of external and internal evaluation. The issue of quality of adult non-formal education monitoring is illustrated with the example of the comparative study which has been implemented within a GOAL project (initiated by Erasmus+ programme Key Action 3), which aims at development of recommendations for the leaders of non-commercial associations dealing with effective development Non-formal adult education in Belgium (Flanders), the Czech Republic, Iceland, the Netherlands, Lithuania and Slovenia. The team of educators and practitioners from these countries has been successfully working on this project since February 2015 through January 2018. Taking into account the need to develop methodological recommendations for analyzing the quality of adult non-formal adult education, the Ukrainian Network for Adult Education and Development of Innovation (Network for Development), has been studying this issue since 2014. The study is based on the following indicators: the quality of the goals and objectives of non-formal education, the quality of the educational program in the field of non-formal education, the quality of the materials and technical base of the educational processes, the quality of the teaching staff, the quality of the information and methodological base, the quality of technological support, the control on quality of the educational process, the quality of the teaching staff motivation, the quality of the attitude of adults towards the process of non-formal education. Indicators of creative activity of adults, level of their cognitive autonomy and creative abilities (productivity of thinking), flexibility, originality, ease of establishment of interdisciplinary connections, practical orientation of cognitive activity are also important criteria for the quality of non-formal education.